PERTUMBUHAN BEBERAPA VARIETAS PEPAYA (Carica papaya L.) PADA BERBAGAI JENIS PUPUK - Yohanis Tambing; Muhardi Muhardi; Dewa Ariembawa (Universitas Tadulako, 2010)
The research aimed to identify the growth of some papaya varieties as affected by various fertilizer applications. The research was carried out from November 2008 to March 2009 in